Differences in neonatal adverse outcomes among women with gestational diabetes mellitus managed by diet or medication: a propensity score matched analysis of a population-based sample - George Mnatzaganian; Marietta Taylor; Fan He; Nicola Yuen; H. David McIntyre; Mark Woodward; Liangkun Ma; Rachel R. Huxley (Taylor & Francis Group, 2023)
Objective Neonatal outcomes in women with and without medically managed gestational diabetes mellitus (GDM) were compared after accounting for differences in maternal baseline characteristics using a propensity score (PS) analysis.Methods Women without preexisting diabetes, delivering singletons during 2010-2017 in a large hospital, were eligible for inclusion. Using nearest-neighbour PS matching, women with non-pharmacological managed GDM were matched with women whose GDM was medically managed. A conditional logistic regression consequently compared the neonatal adverse outcomes between the groups after adjusting for gestational age, induction of labor, birth type, and number of ultrasounds conducted during the pregnancy.Results Of the overall 10028 births, GDM was diagnosed in 930 (9.3%), of whom 710 (76.3%) were successfully matched. The conditional regressions found higher risk of neonatal adverse outcomes in neonates of women with non-pharmacological managed GDM compared to neonates of women with medically managed GDM. These included a higher risk of hypoglycemia (odds ratio (OR) 1.56, 95% confidence interval (CI) 1.03-2.38, p = 0.037), hypothermia (OR 2.29, 95%CI 1.05-5.00, p = 0.037), and birth injuries (OR 3.50, 95%CI 1.62-7.58, p = 0.001), and a higher risk of being small for gestational age (OR 2.06, 95%CI 1.01-4.18, p = 0.046) and being admitted to a special care unit (OR 2.04, 95%CI 1.29-3.21, p = 0.002).Conclusions The increased neonatal morbidity associated with non-medicated GDM identified in our study may indicate that diet and lifestyle changes alone are not sufficient to achieve glycaemic control in some women with GDM. Our findings indicate that gestational diabetes management approach is independently associated with neonatal outcomes.